PENGARUH BEBERAPA JENIS TANAMAN SEMUSIM TERHADAP ALIRAN PERMUKAAN TANAH DI DESA BATU GAJAH KECAMATAN PASIR PENYU KABUPATEN INDRAGIRI HULU - Erwin Febriyandra; Al Ikhsan Amri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to find out the effect of some type of annual plant on the run off and soil erosion that occurred in the village of Batu Gajah, district Pasir Penyu, district upstream Indragiri Hulu. The research was carried out at the Balai Benih Induk (BBI) the village of Batu Gajah, district Pasir Penyu, District Upstream Indragiri Hulu, Riau Province. The research lasted for four month, from February to May 2016. The research was carried out experimentally on land with uniform slope (9%) and used a Randomized Block Design (RBD). The treatment factors are : (P1) = soybean plant, (P2) = peanut plant, (P3) = corn plant, (P4) = mung bean plant. Data were analyzed with further test Duncan’s New Multiple Range Test (DNMRT) at the level of 5%. Parameter observed are rainfall, amount of runoff, soil erosion (sedimentation), infiltration and soil physical properties. Based on the research that the planting of annual plant at the level slope of (9%) showed the effect of variation on the run off and soil erosion (sedimentation), the treatment of mung bean plant is the best effect, showed that the least amount of run off and soil erosion with 15,22 l/plot and 735,18 g/plot.Key words : annual plant, run off, slope land, soil erosion.